An Individualized Red Blood Cell Transfusion Strategy Using Pediatric Perioperative-Transfusion-Trigger Score Reduced Perioperative Blood Exposure for Children: A Randomized Controlled Clinical Trial - Luo Z; Li Y; Li X; Liao R (Dove Medical Press, 2023)
Zhen Luo,1 Yansong Li,2 Xiaoqiang Li,1 Ren Liao1 1Department of Anesthesiology, Sichuan University West China Hospital, Chengdu, People's Republic of China; 2Department of Anesthesiology, Center for Brain Science, The First Affiliated Hospital of Xi'an Jiaotong University, Xi'an, People's Republic of ChinaCorrespondence: Xiaoqiang Li, Email 39006900@qq.comObjective: The optimal red blood cell transfusion strategy for children remains unclear. We developed an individualized red blood cell transfusion strategy for children and tested the hypothesis that transfusion guided by this strategy could reduce blood exposure, without increasing perioperative complications in children.Methods: In this randomized controlled clinical trial, 99 children undergoing noncardiac surgeries who had blood loss of more than 20% total blood volume were randomly assigned to an individualized-strategy group using Pediatric Perioperative-Transfusion-Trigger Score or a control group. The amount of transfused red blood cell was counted, and patients were followed up for postoperative complications within 30 days.Results: Twenty-six children (53.1%) in the individualized-strategy group received transfusion perioperatively, as compared with 37 children (74%) in the control group (p < 0.05). During surgery, children in the individualized-strategy group were exposed to fewer transfusions than in the control group (0.87± 1.03 vs 1.33± 1.20 Red-Blood-Cell units per patient, p = 0.02). The incidence of severe complications in the individualized-strategy group had a lower trend compared to the control group (8.2% vs 18%, p = 0.160). No significant difference was found in the other outcomes.Conclusion: This trial proved that red blood cell transfusion guided by the individualized strategy reduced perioperative blood exposure in children, without increasing the incidence of severe complications. This conclusion needs to be reaffirmed by larger-scale, multicenter clinical trials.Keywords: red blood cell, transfusion strategy, perioperative red blood cell transfusion, pediatrics, hemoglobin concentration